Sistema Web para gestão e elaboração de projetos de recuperação de áreas degradadas : uma avaliação - Ferreira, Jean Carlos (2015)
Due to the gradual increase in the number of environmental licensing procedures in order to recover degraded areas, is expected to become insolvent in the coming years in environmental management. Thus, it becomes imperative to design new web-based technologies that enable innovation in the management of natural resources system, principally for the recovery of degraded areas. Thus, in this study we investigated the application of intelligent systems as an alternative to the decision-making during the development and management of degraded areas recovery projects. The objective of this research is to analyze the impacts to improve the process of preparing and assessment of degraded areas recovery projects using the System Preparation of Degraded Area Recovery Project. The simulation experiments of degraded areas recovery projects prioritized projects in rural properties, which are responsible for the greatest number of processes for regulation and environmental licensing. The applications of experiments in the Degraded Area Recovery Project Development System resulted in the settings for projects of any situation in rural or urban areas, in the description of the experiments, the rules to allow the technical recommendations through combinations of questions and answers in the present description of the flow of regularization processes and environmental licensing with degraded areas recovery projects and the description of an environmental management system, unique to degraded areas. It follows that the Area Recovery Project Development System Degraded, has a positive impact, both for those who analyze the projects, and for those who make them, and proved to be an efficient solution in educational management processes recovery projects of degraded areas. It is an artificial intelligence tool to aid decision making, with an initial database, developing and classified as expert planning system. For further analysis of the environmental impacts of the degraded area, it is for the expert, recommend alternatives that lead to successful recovery of environmental liabilities. This system may have connection with other systems used in environmental management and will aim at ensuring greater efficiency and effectiveness as a whole, lining up, especially with the new rules introduced by legislation.